Rapidly fatal necrotising fasciitis caused by Streptococcus pyogenes. Issue 7 (July 1993) - Donaldson, P M; Naylor, B; Lowe, J W; Gouldesbrough, D R
Abstract : AIMS–To describe the morbid anatomical and bacteriological features in a series of five cases of rapidly fatal Streptococcus pyogenes necrotising fasciitis. METHODS–Post mortem and bacteriological examinations were made of five patients dying within 48 hours from rapidly fatal necrotising fasciitis. RESULTS–All five cases died rapidly from a toxic Streptococcus toxin syndrome as a result of developing necrotising fasciitis following trivial injury. CONCLUSIONS–Necrotising fasciitis caused by Streptococcus pyogenes infection can be rapidly fatal. This is probably the result of a toxic shock syndrome. Rapid, early diagnosis and swift and probably empirical treatment is required to avoid a fatal outcome.